Dinamika Praktik Pembagian Waris Pada Masyarakat Pedesaan; Kajian Sosio-kultural dan Hukum - Ridho, Muhammad (Jurnal EL-QANUNIY: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2025)
Indonesia, as a multicultural nation, is home to diverse ethnic groups, cultures, and value systems, including in the governance of inheritance law. Within this diversity, Islamic inheritance law normatively stipulates that male heirs receive a share twice as large as that of female heirs. However, in practice, not all Muslim communities in Indonesia adhere strictly to these provisions. This study aims to examine the inheritance distribution practices among rural Muslim communities and explore their perspectives on Islamic inheritance law. The research employs a descriptive qualitative approach through field observations, in-depth interviews, and document analysis in a rural village setting. The findings reveal that the local community tends to distribute inherited property, particularly land, equally between male and female heirs (1:1) through family deliberations. This distribution is perceived as a form of social justice that aligns with local values of familial harmony and mutual agreement, despite differing from the normative provisions of Islamic law. These findings reflect a process of contextual adaptation between religious principles and local wisdom in the community's social practices.